Different metal-doped ZnS quantum dots photocatalysts for enhancing the permeability and antifouling performances of polysulfone membranes with and without UV irradiation - Vatanpour, Vahid; Karatas, Okan; Amiri, Saba; Rajabi, Hamid Reza; Koyuncu, Ismail; Khataee, Alireza (Pergamon-Elsevier Science Ltd, 2022)
In this study, the effect of three different transition metal ion dopants (Mn2+, Fe2+, and Co2+) on the characteristics of zinc sulfide (ZnS) quantum dots (QDs) was investigated and the obtained QDs photocatalysts were applied for the modification of polysulfone (PSf) mixed matrix membranes to reduce membrane fouling. The synthesized QDs and fabricated membranes were fully identified with SEM, TEM, AFM, FTIR analyses, and also underwent porosity and contact angle tests. Flux recovery ratios (FRR) significantly increased from 69.8% (bare) to 85.0% (1% Fe-doped ZnS QDs) after modification of membranes with metal-doped QDs. The contact angles of the prepared membranes decreased with doping of dissimilar metals, therefore hydrophilicity increased, and reversible/non-reversible blockages were improved. Besides, the use of UV irradiation during the washing of the membranes increased the FRR of the photocatalytic activated membranes to 91.2%. Compared to the bare PSf membrane in dye solution filtration, 1% Fe-doped ZnS QDs membrane yielded twice as much flux and 15% higher FRR results. Therefore, the results proved that metal-doped QDs can be used in the modification of PSf membranes with high efficiency.
Keywords: Quantum dots; ZnS; Metal-doped ZnS; Membrane modification; Anti-fouling; Dye rejection